Expanding (x+12)(x3) into Standard Form
In mathematics, standard form for a quadratic expression is ax² + bx + c, where a, b, and c are constants. To express the product of (x+12)(x3) in standard form, we need to expand the expression using the distributive property, also known as FOIL (First, Outer, Inner, Last).
Steps to Expand the Expression

Multiply the First terms:
 x * x = x²

Multiply the Outer terms:
 x * 3 = 3x

Multiply the Inner terms:
 12 * x = 12x

Multiply the Last terms:
 12 * 3 = 36

Combine the like terms:
 x²  3x + 12x  36 = x² + 9x  36
Standard Form
Therefore, the expression (x+12)(x3) in standard form is x² + 9x  36.